THE USE OF ELECTROMORFOTHERAPY RESOURCES IN AGED PERSONS - REVISION ARTICLE (Fiep Bulletin - online, 2014)
The electric thermal phototherapeutic agents (electrical, thermical, electromagnetic radiation, etc) are used in the treatment of muscular, articular and neurological dysfunctions of aged persons. It is important to highlight that the use of hot and cold as a therapeutical resource in muscular and skeletal disorders provokes a main dilemma of the physiotherapist professional. The intention of this study is to discuss through a short revision, the utilization of eletromorfotherapy resources in physiological changes of skeletal muscle systems. The study was developed from theses, dissertations, indexed scientific articles, virtual library collects (BIREME/ MEDLINE/ LILACS/ SCIELO), periodicals and scientific magazines recently published. The experts relates that the electric thermal phototherapeutic resources in aged patients must be used with caution, observing the levels and limitations of the geriatrical pathologies, because the behavior success with termic, electric and phototherapeutic agents are depending on a good technical and scientific knowledge of this agents.
Keywords: Thermotherapy; Phototherapy; Electrotherapy; Aged